Impact of Human Behavior According to Social Distance Rules During Covid-19 (Case Study Bukit Bintang - Kuala Lumpur) (American Journal of Agricultural Science, Engineering, and Technology, 2023)
SARS-CoV-2 was linked to COVID-19 in Wuhan, China, in December 2019. After confirmed cases and deaths in numerous countries, WHO proclaimed a global pandemic. During the outbreak, territorial public and private socializing spread the virus quickly with friends, families, and relatives. Hence, this research examines the effectiveness of social distance rules in preventing the spread of COVID-19 in Bukit Bintang, Malaysia, from the perspectives of residents and shopping mall visitors during the recovery Movement Control Order (RMCO period). This study examines space territoriality among Bukit Bintang's foreign workers and mall visitors using qualitative (structured observation) and quantitative (questionnaire) methodologies. Structured observations examine human behavior in uncontrolled (home, neighborhood) and controlled (shopping mall) situations. As part of the quantitative method, a questionnaire survey is utilized to learn about respondents' specific actions, such as personal and public space invasion. This study collects data by purposeful sampling and included 250 people. The study's findings confirm the association between numerous constructs, and indicates that the number of territories people occupy in private and public contexts tends to spread COVID-19 in Bukit Bintang, Malaysia. Social distancing drastically affects COVID-19's spread and number of deaths. According to the study, the virus spreads more when people ignore the social distance rule.